A Novel Generalized Memristor Based on Three-Phase Diode Bridge Rectifier - Chaojun Wu; Ningning Yang; Cheng Xu; Rong Jia; Chongxin Liu (Complexity)
Memristive characteristics in three-phase diode bridge rectifier circuit are proposed in this paper. The conduction of the diodes is discussed and the characteristics of the pinched hysteresis loop are analyzed by both numerical simulations and circuit simulations. The hysteresis loops of each phase not only are pinched at the origin but also have the other two intersection points in the first quadrant and the third quadrant when three-phase bridge rectifier circuit is running under normal operation. Other conditions are also discussed when a variety of faults conditions occur. The simulation results verify that the three-phase bridge rectifier circuit can be described as a generalized memristor element during several operation states.